Digital parenting burdens in China : online homework, parent chats and punch-in culture - Lim, Sun Sun; Wang, Yang (Emerald points., 2024)
The ebook edition of this title is Open Access and freely available to read online. As a world leader in technology, China's adoption of trend-setting innovations has led to the encroachment of digital technologies into the home. Digital Parenting Burdens in China is the first English language book to explore the impact of digitalisation on family life in China, including the phenomenon of 'punch-in culture' and its implications for family wellbeing. In an era of heightened digital connectivity via parent-teacher and parent-parent chatgroups and homework apps, how are Chinese parents coping with the challenges of parental accountability, peer pressure and performative parenting? Delving into 90 interviews from both before and during the Covid-19 pandemic, authors Sun Sun Lim and Yang Wang provide rich vignettes of family life in urban Chinese households in Beijing and Hangzhou to demonstrate how parents appropriate technology as they raise their children, steer them towards the social aspirations of academic achievement, and navigate the rocky terrains of children's home-based learning during the pandemic lockdowns. Empirically grounded and theoretically informed, these vivid accounts serve as valuable insights into understanding how family life around is shifting in the face of digitalisation not only in China, but globally.